Excitons em ponto quântico tipo II de CdTe/CdSe - Sousa, Francisco Etan Batista de (2017)
Quantum Dots (QD’s) have been source of extensive scientific research in the last years. Among many applications of this type of structure, one candidate has been highlighted as a strong substitute for the major source in the current global energy matrix, the Quantum Dot’s Solar Cells (QDSC). In this work the exciting properties of type II CdTe/CdSe QD’s with cylindrical symmetry are investigated. It was developed a computational model that is able to diagonalize a two-particle hamiltonian of the type H(re; rh) =He + Hh + U(|re -rh|), where He;h representing the hamiltonian of individual particles and U(|re - rh|) the Coulomb interaction between electrons and holes. Differently from other methods, that make use of perturbation theory, to determine the binding energy of the fundamental exciton, the present method is able to calculate the excitonic spectrum in a wide range of energies, whose width depends solely on the available computational power. It has been possible to identify a dependence of this proprieties on the confinement dimensions. For the first ten confinement states, lower energy levels are obtained with the increase of the cylindrical well radius and the barrier width along the z-axis. An analysis of the symmetry of the spatial part the wave function was made as well. Our results indicate that we are on the right way to obtain another important data observed on a QDSC, as excitonic lifetime and optic absorption, may reveal to us something about electronic extraction and quantum yield of these materials.